A class of periodic integral equations with numerical solving by a fully discrete projection method - Solodky, S.G.; Semenova, E.V. (Український математичний вісник, 2014)
For a class of integral periodic equations of the first kind the problem of stable approximate solving is considered. The error estimates in the metric of Sobolev spaces for a fully discrete projection method with two discretization parameters are established. For choosing the level of discretization a balancing principle is used.